Organic and inorganic forms of phosphorus in soils amended with sugar cane filter cake - Braos, Lucas Boscov [UNESP]; Bettiol, Aline Carla Trombeta [UNESP]; Di Santo, Ludmilla Geraldo [UNESP]; Ferreira, Manoel Evaristo [UNESP]; da Cruz, Mara Cristina Pessôa [UNESP] (Wiley, 2020)
Studies of phosphorus (P) behaviour in soils receiving sugar cane filter cake are important for determining doses, its contribution to P nutrition and maximizing fertilizer efficiency, especially in soils with low P availability. This study aimed to assess organic and inorganic forms of P in soils treated with sugar cane filter cake, and the relationship between these and plant available P. Soil inorganic (Pi) and organic (Po) phosphorus forms, organic carbon, pH and resin P were measured in two soils; a Typic Hapludox with clay texture and an Arenic Hapludult with loamy sand texture, subject to three fertilizer treatments (nil P control and 100 mg P dm−3 as filter cake and triple superphosphate). Inorganic P was fractionated to soluble/loosely bound, Al-bound, Fe-bound, occluded and Ca-bound P forms. Organic P was fractionated into labile, fulvic, humic and residual Po forms. Plant dry matter yield and P uptake were also determined. Both fertilizers increased the Al- and Fe-bound P fractions, with the increases caused by triple superphosphate 14.7 and 7.2 mg kg−1 higher than filter cake, respectively. Filter cake increased the fulvic Po by 40.9 mg kg−1, while triple superphosphate increased it by 28.5 mg kg−1, in the fine-textured soil. Al-, Fe-bound and labile Po fractions in both soils had significant correlations (p <. 01) with plant absorbed P (r =.75,.84 and.54, respectively). Filter cake resulted in lower Pi fractions and availability, and it has potential to partially replace mineral P fertilizer in fine-textured soils and, entirely, in coarse-textured soils.
Keywords: available P; NMR spectroscopy; organic fertilizer; phosphorus cycling; phosphorus fractions